Culture, institutions, and light output of the sun - Aqil Luqman Nurhakim (2017)
We study whether the variation in the intensity of ultraviolet radiation (UVR), which has been shown to be the root of a number of diseases, can explain the substantial differences in institutional quality across the globe. Evidence suggests that UVR has a negative and significant effect on institutional quality. The results of this study further indicate that UVR affects institutional quality through two cultural channels, namely: individualism and religiosity. Generalised trust, however, was found to be an insignificant channel through which UVR affects the quality of a country’s institutions. Finally, we present further evidence that UVR may be a suitable instrument for investigating the relationship between institutions and income. Altogether, these results lend support to the notion that disease ecology matters for institutional development, which is consistent with the well-established disease endowment hypothesis introduced by Acemoglu et al. (2001). Our paper contributes to the literature in three ways. Firstly, our findings are complementary to the findings of Andersen et al. (2016) who found that UVR and income were negatively related, as it is plausible that UVR affects income through institutions, an area unexplored by their study. Secondly, our findings also suggest that UVR may influence institutions through culture. Finally, we show that UVR may prove to be a better instrument for institutions than the settler mortality variable used by Acemoglu et al. (2001) in exploring the relationship between institutions and income.